Becoming A Mother: The Transition to Motherhood in Chimamanda Ngozi Adichie’s Zikora - Roifah, Miftahur (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2021)
In patriarchal society, motherhood is viewed as a responsibility for women although not all are willing or able to carry it on. To become a mother, a woman has to experience a challenging phase in life and ready to sacrifice everything they have. Feminist critics see motherhood as a complex issue operating patriarchal institution that regulates, dominates, and oppresses women. What is more, some women are not ready with the consequences during the transition to motherhood and bear the status of becoming a mother that often results in having a hard time. To bring this issue into discussion, this study is going to explore the crises that Zikora has to undergo in her transition to become a mother. Zikora is the protagonist in Chimamanda Ngozi Adichie's short story, Zikora. In analyzing the issue, this study applies the theory of motherhood by Andrienne Rich and uses a qualitative approach with a close reading method. The result of the study shows that motherhood brings women to a new world full of challenges. Motherhood requires not only physical strenght but also mental strenght and self control so that whatever the crises are, women can bear them and overcome the obstacles they are facing.